PLEASE (Pick, List, Evaluate, Activate, Supply, End): An Effective Strategy for Teaching Writing - Wahyuningtyas, Irsa Nabila Tri; Zuhriyah, Mukminatus (Teaching English as Foreign Language, Literature and Linguisticss, 2024)
The students of class VII of one of state junior high schools in Jombang got difficulty in their descriptive writing class so that their ability to write was low. It was caused by the monotonous teaching strategy used by the English teacher in their writing class. So that the researchers are interested in conducting a study by implementing PLEASE (Pick, List, Evaluate, Activate, Supply and End) strategy for teaching writing in that class. The purposes of this study were to know: 1) the students’ writing ability before being taught using PLEASE; 2) the students’ writing ability after being taught using PLEASE and 3) the effectiveness of PLEASE for teaching writing. This study used a pre-experimental research design with the population of all the students in class VII consisting of students. Meanwhile, the sample was 29 students of class VII B taken by a purposive sampling. The data were collected from the pre-test and post-test of writing descriptive texts. The data were analysed using a statistical descriptive and a paired-sample t-test. The results of this study showed that: 1) the students’ writing ability before using PLEASE strategy was low with the average score of 57, 2) the students’ writing ability after using PLEASE strategy was excellent with the average score of 86 and 3) the use of PLEASE strategy was effective for teaching writing with the significant score of sig. (2-tailed) was o.ooo. Based on the results of this study, the researchers hope that the Engish teachers and students implement PLEASE strategy in their writing classes.